Connexin and pannexin hemichannels in brain glial cells: properties, pharmacology, and roles - Giaume, Christian; Leybaert, Luc; Naus, Christian, C; Sáez, Juan-Carlos (Frontiers in Pharmacology, 2013)
Functional interaction between neurons and glia is an exciting field that has expanded tremendously during the past decade. Such partnership has multiple impacts on neuronal activity and survival. Indeed, numerous findings indicate that glial cells interact tightly with neurons in physiological as well as pathological situations. One typical feature of glial cells is their high expression level of gap junction protein subunits, named connexins (Cxs), thus the membrane channels they form may contribute to neuroglial interaction that impacts neuronal activity and survival. While the participation of gap junction channels in neuroglia interactions has been regularly reviewed in the past, the other channel function of Cxs, i.e. hemichannels located at the cell surface, has only recently received attention. While gap junction channels provide the basis for a unique direct cell-to-cell communication, Cx hemichannels allow the exchange of ions and signaling molecules between the cytoplasm and the extracellular medium, thus supporting autocrine and paracrine communication through a process referred to as “gliotransmission”, as well as uptake and release of metabolites. More recently, another family of proteins, termed pannexins (Panxs), has been identified. These proteins share similar membrane topology but no sequence homology with Cxs. They form multimeric membrane channels with pharmacology somewhat overlapping with that of Cx hemichannels. Such duality has led to several controversies in the literature concerning the identification of the molecular channel constituents (Cxs versus Panxs) in glia. In the present review, we up-date and discuss the knowledge of Cx hemichannels and Panx channels in glia, their properties and pharmacology, as well as the understanding of their contribution to neuroglia interactions in healthy and diseased brain.